2015
DOI: 10.2105/ajph.2014.302076
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Diversity in the Public Health Research Workforce: The Research and Mentorship Program for Future HIV Vaccine Scientists

Abstract: A multicomponent, mentored research experience that engages medical students from underrepresented communities and is organized within a clinical trials network may expand the pool of diverse public health scientists. Efforts to sustain scholar interest over time and track career trajectories are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 23 publications
0
41
0
Order By: Relevance
“…In addition, mentored research programs that are dedicated to increasing workforce diversity should have national reach to attract prospective students, and therefore program stipends should cover travel and living expenses to ensure promising candidates receive high quality immersion experiences. A clinical trial network-based mentored research program designed to attract medical students of color into HIV vaccine science was successful in marshaling these resources which was perceived by both mentors and mentees to be instrumental in the program’s early success (44). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, mentored research programs that are dedicated to increasing workforce diversity should have national reach to attract prospective students, and therefore program stipends should cover travel and living expenses to ensure promising candidates receive high quality immersion experiences. A clinical trial network-based mentored research program designed to attract medical students of color into HIV vaccine science was successful in marshaling these resources which was perceived by both mentors and mentees to be instrumental in the program’s early success (44). …”
Section: Discussionmentioning
confidence: 99%
“…8 Access to research mentorship at the undergraduate, graduate and post-doctoral levels, as well as during early career is critically important to the development of an independent research career 18 . Yet, institutions with the mission of educating predominantly racial/ethnic minority students such as Historically Black Colleges and Universities (HBCU), Institutions with High Hispanic Enrollment (HHE), and Tribal Colleges (TC) are severely underfunded compared with mainstream institutions of higher education.…”
Section: Institutional Determinants Of Successful Transitionmentioning
confidence: 99%
“…The Puerto Rico Comprehensive Center for the Study of HIV Disparities and the Mentoring Institute for HIV and Mental Health matches mentees with expertise in collaborating institutions [58]. Creating structured opportunities for training and research experience with senior mentors has also shown positive results in engaging minority students in HIV research [10,85]. For example, an analysis of the Research and Mentoring Program (RAMP) for minority medical students working in the international HIV Vaccine Trials Network showed significant improvements in self-reported knowledge and professional skill-related areas such as scientific writing.…”
Section: Creating An Infrastructure To Address the Challenges Faced Bmentioning
confidence: 99%
“…For example, an analysis of the Research and Mentoring Program (RAMP) for minority medical students working in the international HIV Vaccine Trials Network showed significant improvements in self-reported knowledge and professional skill-related areas such as scientific writing. Furthermore, there was a significant increase in the proportion of participants who reported an intention to pursue a career in HIV/AIDS research, and a belief that such opportunities were open to program participants [85]. The Visiting Professors Program at the University of California at San Francisco (UCSF), through the Center for AIDS Prevention Studies, supports faculty focused on HIV prevention research in minority communities [86].…”
Section: Creating An Infrastructure To Address the Challenges Faced Bmentioning
confidence: 99%